Angiomyolipoma at the base of the tongue: A type of mucocutaneous angiomyolipoma. Issue 6 (November 2016) - Morisaki, Tsuyoshi; Moritani, Sueyoshi; Takenobu, Masao; Kashu, Ippei; Koyama, Satoshi; Fukuhara, Takahiro; Kitano, Hiroya; Takeuchi, Hiromi
Abstract: Angiomyolipomas (AMLs) are a type of mesenchymal tumor often arising in the kidneys. AML is known for its strong association with tuberous sclerosis. AMLs are rarely found in the head and neck region. An AML at the base of the tongue has not been reported in past research. We report the case of a 72-year-old man with an AML at the base of the tongue. Furthermore, we performed a literature review to clarify the characteristics of such an AML. According to our review, AMLs at the base of tongue has clinical and morphological similarity with the mucocutaneous AML which never associates with tuberous sclerosis. We report the first case of an AML at the base of the tongue. An AML at the base of the tongue is clinicopathologically distinct from a renal AML.